EVALUATION OF ANTIBIOTIC SUSCEPTIBILITY OF ANAEROBIC PATHOGENS BACTEROIDES, PREVOTELLA AND FUSOBACTERIUM ISOLATED FROM CANCER PATIENTS - I. I. Shilnikova; N. V. Dmitrieva (Сибирский онкологический журнал, 2016)
In this study 122 strains of strictly anaerobic gram-negative rods Bacteroides, Prevotella and Fusobacterium, isolated from cancer patients between 2004 and 2014 were analyzed. The most common strains were B. fragilis (55 %) followed by Prevotella (34.4 %) and Fusobacterium spp (10.6 %). The species identification was carried out by matrix-assisted laser desorption ionization time of flight mass spectrometry (MALDI-TOF MS). Among the B. fragilis group strains, B. fragilis, B. thetaiotaomicron, B. ovatus and B. vulgatus were isolated most frequently. Among Prevotella species, the most frequently isolated species were P. buccae, P. buccalis, P. oris, P. denticola and P. nigrescens, and 77 % of the Fusobacterium spp. were F. nucleatum. Susceptibilities of the isolates to antimicrobial agents were determined by the E-test methodology. The percentage of the susceptibility of B. fragilis group isolates were: metronidazole, 97 %; imipenem, 95.5 %; amoxicillin/clavulanate, 95.5 % and clindamycin, 77.6 %. Three B. fragilis isolates proved to be multidrug-resistant (simultaneously to imipenem, amoxicillin/ clavulanate and metronidazole or clindamycin). All Prevotella isolates were susceptible to imipenem and amoxicillin/clavulanate, whereas 78.6 % of the pigmented Prevotella species and 46.4 % of the non-pigmented species were resistant to penicillin. The number of strains susceptibility to metronidazole and clindamycin were 93 % and 88 %, respectively. All Fusobacterium strains were sensitive to all tested antibiotics, including penicillin.